Iron Deficiency Anemia in Female Workers: A Critical Occupational Health Priority - Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Iron deficiency anemia (IDA) is a major occupational health concern among female industrial workers in Indonesia, with prevalence reaching 24–46%. It affects productivity, safety, and gender equity.Methods: Narrative review of national surveys, WHO reports, and peer-reviewed studies on IDA prevalence, determinants, and workplace interventions.Results: Evidence shows IDA reduces endurance, cognitive performance, and reaction time, increasing accident risk. Current workplace programs remain inconsistent and poorly integrated into occupational health systems.Conclusions: IDA prevention should be mandated as part of occupational health policy through surveillance, supplementation, and nutrition programs to protect workers and improve productivity.